Simon Called Peter - Keable, Robert, 1887-1927 (Salt Lake City, UT : Project Gutenberg, 2005)
"Simon Called Peter" by Robert Keable is a novel published in 1921. This controversial bestseller tells the story of Peter Graham, a priest who has an affair with a nurse named Julie during wartime France. Torn between faith and love, Peter faces a spiritual crisis that leads to a profound revelation. The novel's frank treatment of sexual and religious themes sparked controversy while selling over 600,000 copies in the 1920s. It even earned a mention in F. Scott Fitzgerald's "The Great Gatsby." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Simon_Called_Peter
Release date is 2005-01-03
Produced by Juliet Sutherland, Mary Meehan, and the Online Distributed Proofreading Team
Keywords: World War, 1914-1918 -- Fiction